(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Compressive and split tensile strengths of steel fiber reinforced concrete (SFRC) subjected to temperature (20, 100, 200, 400 and 600 oC) were experimentally investigated in this study. Four different volume percentages (0, 0.25, 0.5 and 0.75% by volume of concrete) of steel fibers were used. Concrete specimens were cured in water for 28 days and then allowed to dry for three days at laboratory temperature before subjected to heat for 2 hours in an electric furnace. After the completion of heating period, specimens were cooled down for 1 day at laboratory conditions and then tested for determining their compressive and split tensile strengths as well as ultrasonic pulse velocity (UPV). The relation between concrete strengths and temperature for steel fiber reinforced concrete (SFRC) were also discussed. The test results show that the compressive and split tensile strengths of steel fiber reinforced concrete are less affected by temperature as compared to those of control concrete (without fiber). The results of statistical analysis show a good linear relation between: 1) Compressive strength and temperature; 2) Split tensile strength and temperature for SFRC.